(untitled) (المجلة الدولية للبحوث العلمية, 2023)
Cardiovascular diseases (CVDs) are the main cause of morbidity and mortality with an estimation of 17.9 million deaths around the world annually. Student’s Knowledge about the associate risk factors will help in changes individuals’ health behaviors and lifestyle practices in their life. Objective: This study tries to find out the relationship between students’ knowledge and selected socio-demographic variables in regard to the risk factors of CVDs. Methods: Descriptive-across section study was conducted with regular undergraduate students at Jibla university for Medical & Health Sciences, Yemen. Convenience sampling technique is used to recruit the participants from each college in this study. Results: A total of 309 students were recruited in this study. Data analysis found that most participants (79%) under age 20 years, the mean age is 22.1±2.3, more than half (57.3%) are females, 71.2%of students are from rural areas, and the majority of participants (87.7%) are married and less than third (31.4%) of them are from the Faculty of Medicine. Moreover, the majority of participants reported that the risk factors of cardiovascular diseases are obesity, high cholesterol, old age, and passive smoking (93,8%, 91.9%, 90.9%, and 90.3% respectively). Regarding the total score, there are statistically significant differences between subject study, age, and place of residence with P-value = <5 (0.000, 0.003, and 0.008 respectively). Except marital status and sex not significant was noted with P-value= <5 (0.256, and 0.678 respectively). Conclusion: The majority of participants have good knowledge regarding to associate risk factors of cardiovascular diseases. The participants showed low knowledge in regard to the high HDL, heredity, high BP, and Irregular eating food.